Contributions of Nonleaf Organs to the Yield of Cotton Grown with Different Water Supply - Dongxia Zhan; Ying Yang; Yuanyuan Hu; Yali Zhang; Honghai Luo; Wangfeng Zhang (The Scientific World Journal)
The objectives of this experiment were (i) to determine the effect of water supply on the photosynthetic capacity of leaves, bracts, capsule walls, and stalks of cotton at different growth stages and (ii) to determine the contributions of these nonleaf organs to whole plant photosynthesis. Water deficit reduced the total surface area per plant but increased the proportion of nonleaf to total plant surface area. Net photosynthetic rates of leaves declined rapidly beginning 25 days after anthesis. In contrast, the net photosynthetic rates of bracts and capsule walls were insensitive to soil moisture stress and decreased by a small amount between 25 and 45 days after anthesis. The relative contribution of bracts and stalks to canopy apparent photosynthesis (CAP) increased under water deficit conditions. Cotton seed weight in the conventional irrigation treatment decreased by 10.1–29.7% when the bolls (capsule walls plus bracts) were darkened and by 5.3–9.9% when the stalks were darkened. On a percentage basis, both boll photosynthesis and stalk photosynthesis contributed more to seed weight when the plants were grown under water deficit conditions rather than nondeficit conditions. In conclusion, nonleaf organs contribute significantly to yield when cotton plants are under water stress during late growth stages.